Pengolahan Limbah Tempurung Kemiri Sebagai Adsorben Senyawa Etilen Dengan Penambahan Kalium Permanganat (KMnO4) - Harits Fadhillah Immaduddin; Shafwan Amrullah; Nurkholis; Theresia Evila Purwanti Sri Rahayu (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Candlenut (Aleurites mollucana) is one of the biggest potentials, especially in Sumbawa Regency. Apart from being a spice, Candlenut also produces waste in the form of shells with a very large carbon content. So that in this study, the use of candlenut shells as adsorbent was carried out using potassium permanganate or KMnO4. The way it works in this research is by doing a charcoal process on the hazelnut shell waste as the carrying substance. Basically, there are 3 stages in this research, including the carbonization of candlenut shells so that they become charcoal using a drum furnace that has been designed by yourself. Subsequently, the composite beads were sieved by using a 100 mesh sieve. Then KMnO4 is added to the mashed charcoal. The variations in the weight of KMnO4 used are 15 grams, 30 grams, and 45 grams. At the test stage, it was carried out by testing the chemical characteristics of the water content, ash content, and analysis of the best samples. At the end of the study, physical and chemical tests were also carried out on composite beads. The results showed that the best water and ash content was found in the amount of addition of KMnO4 compound at 15 grams, namely 7.33% and 7%, respectively. These results indicate that composite bead products have met the SNI 06–3730-1995 standards. For the effectiveness of absorption of ethylene compounds, the resulting composite beads required 15 grams of KMnO4 for the best absorption of 6.1% ethylene.